Is basic capability important enough to distinguish between groups of different competitive performance levels in wild-water slalom? - Ušaj, Anton (Kinesiologia Slovenica, 2001)
The aim of the study was to test a hypothesis that paddlers in wild-water slalom, who reached a higher level of competitive performance (Olympic games level), also have a higher level of basic endurance and basic speed endurance performance than those who compete on lower levels. Four groups of four paddlers were tested: National Olympic team (OLYMPIC), a group of paddlers in the national team who failed to qualify for the Olympic games (NON-OLYMPIC), a group of national juniors group (JUNIOR A) and a group who failed to be selected to the national juniors group (JUNIOR B). All performed two tests: incremental paddling test on flat water for assessment of basic endurance performance and "8" test for assessment of basic speed endurance performance. The results showed that basic endurance characteristics: vsubLT, vsubOBLA and vsubmax and basic speed endurance characteristic tsub8 did not differentiate the OLYMPIC group (2.26plus minus0.02 m/s, 2.37plus minus0.05 m/s, 2.58plus minus0.07 m/s, 110.5plus minus7.1 s) from the NON-OLYMPIC (2.26plus minus0.07 m/s, 2.39plus minus0.08 m/s, 2.62plus minus 0.04 m/s, 113.1plus minus 1.6 s). The results showed that both groups were so close, according to results, that they practically represented a homogeneous single group. Significant differences occurred when the OLYMPIC group was compared to JUNIORS A (2.17plus minus0.06 m/s (P<0.05), 2.27plus minus0.08 m/s, 2.47 plus minus0.07m/s, 121.2plus minus5.7 s), but only in vLT and JUNIORS B (2.07 0.02 mžs (P<0.01), 2.18plus minus0.09 m/s (P<0.01),2.37plus minus0.09 m/s (P<0.01), 126.5plus minus3.5 s (P<0.01)). When both seniors groups were combined into one SENIOR group, then the differences with each of the juniors groups became highly significant in all the parameters. Therefore, the hypothesis of the study was supported. When the differences between paddlers in competitive performance became substantial, then basic endurance and basic speed endurance performance followed suit.
Keywords: hitrostna vzdržljivost; kajak na divjih vodah; kajakaši; raziskave; vzdržljivost